The Stability Improvement of α-Amylase Enzyme from Aspergillus fumigatus by Immobilization on a Bentonite Matrix - Yandri Yandri; Ezra Rheinsky Tiarsa; Tati Suhartati; Heri Satria; Bambang Irawan; Sutopo Hadi (Biochemistry Research International)
The stability of the α-amylase enzyme has been improved from Aspergillus fumigatus using the immobilization method on a bentonite matrix. Therefore, this study aims to obtain the higher stability of α-amylase enzyme from A. fumigatus; hence, it is used repeatedly to reduce industrial costs. The procedures involved enzyme production, isolation, partial purification, immobilization, and characterization. Furthermore, the soluble enzyme was immobilized using 0.1 M phosphate buffer of pH 7.5 on a bentonite matrix, after which it was characterized with the following parameters such as optimum temperature, Michaelis constant (KM), maximum velocity Vmax, thermal inactivation rate constant (ki), half-life (t1/2), and the change of energy due to denaturation (ΔGi). The results showed that the soluble enzyme has an optimum temperature of 55°C, KM of 3.04 mg mL−1 substrate, Vmax of 10.90 μmole mL−1 min−1, ki of 0.0171 min−1, t1/2 of 40.53 min, and ΔGi of 104.47 kJ mole−1, while the immobilized enzyme has an optimum temperature of 70°C, KM of 8.31 mg mL−1 substrate, Vmax of 1.44 μmole mL−1 min−1, ki of 0.0060 min−1, t1/2 of 115.50 min, and ΔGi of 107.37 kJ mole−1. Considering the results, the immobilized enzyme retained 42% of its residual activity after six reuse cycles. Additionally, the stability improvement of the α-amylase enzyme by immobilization on a bentonite matrix, based on the increase in half-life, was three times greater than the soluble enzyme.